2007
DOI: 10.3177/jnsv.53.198
|View full text |Cite
|
Sign up to set email alerts
|

Safety Assessment of PureSorb-QTM40 in Healthy Subjects and Serum Coenzyme Q10 Level in Excessive Dosing

Abstract: Summary PureSorb-Q TM 40 (water-soluble type CoQ 10 powder, CoQ 10 content is 40 w/ w%; hereinafter referred to as P40) is reported in the single-dose human and rat studies to have a greater absorption rate and absorbed volume of CoQ 10 even taken postprandially, than those of regular CoQ 10 , which is lipid-soluble and generally taken in the form of soft-gel capsules. Thus, it was anticipated that the serum CoQ 10 level might be higher with P40 tablets than with soft-gel capsules, even for the same dose of Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Overall, a total of 3697 studies were retrieved from a search of databases, and after title and abstract screening, 2701 were excluded. Evaluation of 81 full-text reports resulted in identification of 40 randomized controlled trials articles 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 that could be included in the analysis. Reasons for exclusion included duration <2 weeks ( n = 16), inappropriate placebo in control group ( n = 10), intervention included CoQ10 and other factors ( n = 12), and article cannot be obtained ( n = 3).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, a total of 3697 studies were retrieved from a search of databases, and after title and abstract screening, 2701 were excluded. Evaluation of 81 full-text reports resulted in identification of 40 randomized controlled trials articles 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 that could be included in the analysis. Reasons for exclusion included duration <2 weeks ( n = 16), inappropriate placebo in control group ( n = 10), intervention included CoQ10 and other factors ( n = 12), and article cannot be obtained ( n = 3).…”
Section: Resultsmentioning
confidence: 99%
“…Although the findings are not yet consistent, they suggest a potential link between them. Two intervention studies conducted in healthy population indicated that high doses of CoQ10 (900 mg/day) over a duration of 4 weeks did not have a significant impact on BP [21,22]. While focusing on the cardiometabolic diseases population, our recent dose-response meta-analysis of twenty-six RCTs with durations ranging from 1 to 24 months showed that CoQ10 supplementation significantly decreased SBP (WMD: −4.77 mmHg; 95% CI: −6.57 to −2.97) with a clinically optimal dose of 100-200 mg/day [10].…”
Section: Discussionmentioning
confidence: 99%
“…Because of its lipophilia, CoQ 10 is poorly absorbed in humans when taken orally, especially under fasting conditions ( 15 , 16 ). Therefore, various methods of emulsification with modified food starch ( 17 ), lecithin ( 18 ), gum arabic ( 19 ), or polysorbate 80 ( 18 , 20 ), or inclusion of ␥ -cyclodextrin ( 15 ), have been used to decrease the hydrophobicity of CoQ 10 . The strategy of emulsification of drugs to decrease hydrophobicity and boost bioavailability has already been used and reported ( 21 , 22 ).…”
mentioning
confidence: 99%